2006
DOI: 10.1002/app.24391
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl polymerization of norbornene over supported nickel catalyst

Abstract: A series of nickel complexes, bis(salicylideneiminato)nickel(II), were supported on spherical MgCl 2 and SiO 2 . Scanning electron microscopy, energy-dispersed X-ray spectroscopy, and the BET method for surface areas measurements were utilized to examine the supporting process of the catalysts. The particle morphology of the original support is retained and replicated throughout the supported catalyst preparation and norbornene polymerization. Spherical polymer particle morphology was achieved, without reactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The bis(salicylideneiminato)nickel(II) complexes Ni-82, Ni-83, Ni-95, Ni-98 and Ni-100 were supported on spherical MgCl 2 and silica [162]. The activities of the supported precatalysts Ni-82, Ni-83 and Ni-98 were in the range of 10 5 g polymer /mol Ni h and significantly higher than those of the supported compounds Ni-95 and Ni-100.…”
Section: No-(ns-)chelate Ligandsmentioning
confidence: 77%
See 2 more Smart Citations
“…The bis(salicylideneiminato)nickel(II) complexes Ni-82, Ni-83, Ni-95, Ni-98 and Ni-100 were supported on spherical MgCl 2 and silica [162]. The activities of the supported precatalysts Ni-82, Ni-83 and Ni-98 were in the range of 10 5 g polymer /mol Ni h and significantly higher than those of the supported compounds Ni-95 and Ni-100.…”
Section: No-(ns-)chelate Ligandsmentioning
confidence: 77%
“…The polymerizations of norbornene were performed in toluene and hexane with the former producing slightly higher yields. In general, the polynorbornenes produced with the supported catalyst had higher molecular weights and slightly broader molecular weight distributions than with the respective homogeneous catalyst [162].…”
Section: No-(ns-)chelate Ligandsmentioning
confidence: 95%
See 1 more Smart Citation
“…These systems were obtained by oxidative addition of salicylaldimine ligands to [Ni(cod) 2 ] (cod = 1,5-cyclooctadiene) and subsequent activation with MAO [14,15]. The systems of some naphtocyimine-nickel complexes/MAO were reported that can catalyze norbornene to polymerization with high catalytic activity [16,17], but there are little reports that these catalyst systems are utilized for polymerization of MMA. Other systems are known [18] but generally, activation by MAO is necessary.…”
Section: Introductionmentioning
confidence: 98%
“…Of them, most are involved in bidentate ligandderived complexes. [53][54][55][56][57][58][59][60][61] A few nickel and palladium complexes based on tridentate ligands were reported for NB polymerization, [62][63][64][65] except limited examples related to oligomerization of ethylene. [66][67][68][69][70][71] For developing new late-metal olefin polymerization catalysis, we designed and synthesized the nickel and palladium complexes based on 4,6-di-tert-butyl-2-(N-(quinolin-8-yl)iminome thyl)phenol (LH).…”
Section: Introductionmentioning
confidence: 99%